Watching the watchers : Parliament and the intelligence services - Bochel, Hugh.; Defty, Andrew; Kirkpatrick, Jane.; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This study offers the first detailed examination of the varied means by which parliament through its committees and the work of individual members has sought to scrutinise the British intelligence and security agencies and the government's use of intelligence.
Keywords: Science